Third-Person Perception, Optimistic Bias, Safer-Sex Campaigns, and Sexual Risk-Taking among Minority "At-Risk" Youth - Chapin, John. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1999)
Recent third-person perception articles suggest that optimistic bias is the mechanism underlying the perceptual bias, but fail to empirically test the assumption. Minority "at-risk" youth are neglected in both literatures, despite the fact that they are frequently the target audience for the resulting campaigns. This study sought to bridge a gap between communication and psychology by determining to what extent third-person perception and optimistic bias co-vary in a sample of 231 urban, minority "at-risk" youth in grades 4 through 12 in urban New Jersey public schools. Findings confirm that third-person perception and optimistic bias are present in the sample. Contrary to the position that optimistic bias causes third-person perception, the findings suggest that a small inverse relationship emerged: 51% of the middle school and high school students surveyed exhibited third-person perceptions (believing they were less influenced by televised safer-sex messages than were their peers), and these students were less optimistic about there chances of becoming HIV infected than their peers; 34% exhibited first-person perceptions (believing they were more influenced by the messages than were peers), and these students were more optimistic than their peers were concerning HIV infection. The remaining 15% perceived no difference between themselves and peers in terms of message influence. Most students (89%) exhibited optimistic bias regarding their chances of avoiding HIV infection in the future. Contains 97 references and 4 tables of data. (Author/RS)
ERIC Note: Paper presented at the Annual Meeting of the Association for Education in Journalism and Mass Communication (82nd, New Orleans, LA, August 4-7, 1999).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adolescents; At Risk Persons; Comparative Analysis; Intermediate Grades; Media Research; Public Health; Safe Sex; Secondary Education; Sex Education; Student Attitudes; Public Service Advertising -- Third Person Effect; New Jersey -- Optimism; Reports, Research; Speeches/Meeting Papers